Hybrid kenaf fibre composite plates for potential application in shear strengthening of reinforced concrete structure - Alam, M.A.; Alriyami, K.; Muda, Z.C.; Jumaat, Mohd Zamin (Indian Society for Education and Environment, 2016)
This paper presents the finding of an experimental study on kenaf fibre hybrid composite plates for potential application in shear strengthening of RC beam. In the experimental programme, hybrid composite plates had been fabricated using kenaf and carbon fibres with five different mixes i.e., 47% kenaf with 0% carbon; 45% kenaf with 2.5% carbon; 47% kenaf with 5% carbon; 45% kenaf with 7.5% carbon and 45% kenaf with 10% carbon. The physical and mechanical properties of the fabricated hybrid composite plates were then experimentally investigated. Results showed that carbon contents had an influence to enhance the tensile strength of the plates. Hybrid composite plate with 10% carbon content had shown 130% higher tensile strength as compared to that of plate without carbon fibre. The carbon content also had enhanced the modulus of elasticity of plates. Higher percentage of carbon had shown higher tensile strength and modulus of elasticity of hybrid composite plates. All fabricated plates had linear elastic properties under tension. The density of plates increased with the increasing of carbon content in composite plates. The research findings indicated that the developed hybrid composite kenaf could be used for shear strengthening of reinforced concrete beam.